From pollution to misuse: understanding RTIs in Pakistan - Nafia Hijab; Muhammad Rafay Khan; Khushboo Nusrat (Journal of the Pakistan Medical Association, 2025)
Dear Editor, Respiratory infections, including the common cold, pharyngitis, sinusitis, and pneumonia, are especially prevalent among immunocompromised populations. From 1990 to 2019, Pakistan experienced the fastest increase in respiratory infections among Asian countries, surpassing India, Bangladesh, and China. (1) Several factors contribute to this surge. Pakistan ranks second globally for poor air quality, which is significantly linked to respiratory tract infections. (2) Rapid urbanisation and the use of biomass fuel in slums and rural areas have led to substandard living conditions, increasing the incidence of respiratory infections. (3) Misuse of antibiotics has also resulted in antibiotic-resistant organisms, raising morbidity and healthcare costs. (4) Strategies to combat respiratory infections amid air pollution include encouraging public transportation, wearing masks, improving ventilation, limiting outdoor activities on high-pollution days, and implementing green infrastructure and urban planning. Additionally, improving ventilation and reducing biomass fuel use in slum areas is essential. (2,3) Antimicrobial resistance, worsened by overprescribing antibiotics, is a major global issue. Interventions should enforce policies against over-the-counter sales, implement stewardship programs, involve clinicians in audits, use rapid point-of-care tests, promote delayed prescribing, improve patient communication, and conduct primary care studies on outcomes. (4)